How to be a sales superstar : break all the rules and succeed while doing it - Tewart, Mark, 1961- (Wiley, 2008)
Making the sale is tougher than. That's why sales professionals and business owners who want to be the best need more than just smooth talk to make it in the sales business. Selling is a job that requires an updated toolkit for real, lasting success. This practical guide teaches you all the specialized skills you need to be a sales superstar. You'll learn how to better understand prospects, master the skills to draw in new customers, and discover the secret to closing any deal.